Hubungan antara Supervisi dengan Pendokumentasian Asuhan Keperawatan di RSI NU Demak - Ardyan Dwi Cahyo; Dyah Wiji Puspita Sari; Muh. Abdurrouf (NAJ Nursing Applied Journal, 2025)
Nursing care documentation plays a crucial role in nursing practice as it serves as legal evidence, a means of communication between healthcare professionals, and an indicator of service quality. However, nurses' compliance with documentation often faces various obstacles. Supervision by nursing managers is seen as an important strategy to ensure documentation implementation complies with applicable standards. This study aims to analyze the relationship between supervision and nursing care documentation at RSI NU Demak. The study used a quantitative method with a cross-sectional design. A sample of 83 inpatient nurses was selected through proportional random sampling from a population of 107 nurses. The research instruments were a supervision questionnaire (17 items) and nursing documentation (20 items) whose validity and reliability have been tested. Data analysis was performed using the Chi-Square test with a significance level of p<0.05. The results showed that the majority of respondents were aged <30 years (53%), were female (89.2%), had a Diploma 3 Nursing degree (51.8%), and had worked for <9 years (53%). Good supervision was found in 60.2% of respondents, while good documentation was found in 59.0%. The Chi-Square test results yielded a p-value of 0.000 (p<0.05) with a correlation coefficient of r=0.981, indicating a very strong relationship between supervision and nursing documentation. Therefore, it can be concluded that there is a significant relationship between supervision and nursing care documentation, where the better the supervision provided, the higher the quality of the documentation produced. The results of this study reinforce the importance of the managerial role in improving the quality of nursing services, especially in terms of care documentation. Effective supervision not only functions as a control tool but also becomes a means of developing and strengthening nurses' competencies in meeting nursing practice standards. With structured and continuous supervision, nurses tend to be more disciplined, accurate, and consistent in documenting every nursing intervention they perform.